Frequency and factors associated with women’s mistreatment in obstetric units in Guinea - Balde, Mamadou Dioulde; Diallo, Ramata; Kourouma, Kabinet; Keita, Kaba Saran; Sidibe, Tiany; Camara, Sadan; Toure, Madeleine; Barry, Fanta; Camara, Bienvenu Salim; Kourouma, Karifa; Diallo, Aissatou; Sall, Alpha Oumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In Guinea, women’s mistreatment during maternal health care remains under-documented. The aim of this study was to analyse the frequency and factors associated with mistreatment in obstetric units in Guinea. Methods: This was a cross-sectional analytical study conducted in January and February 2023 in five prefectures from the country’s different regions. A total of 324 women were surveyed on discharge from obstetric consultations/care. Factors associated with mistreatment were identified using multivariate logistic regression with a p value ≤5%. Analysis was performed using Stata 16.0. Results: One-third of the women surveyed reported having suffered mistreatment in the antepartum period, during labour and/or in the postpartum period. In addition to physical and verbal violence, several other types of mistreatments were reported, including neglect, informal payment and lack of consent. Women receiving care from a midwife were six times more likely to experience physical violence than those receiving care from a physician (p=0.009). Those who went to a prefectural hospital were three times more likely (p=0.05) to suffer such violence than those who went to a regional hospital. Women with no formal education were 90% less likely to be verbally abused than those with higher education (p=0.03). Women living in rural areas were 70% less likely to suffer other types of mistreatments than those living in urban areas (p=0.01). Those who went to a rural health centre or a prefectural hospital were six times and 4.5 times more likely to be subjected to these types of mistreatments, respectively, than those who went to a regional hospital. Conclusions: Prioritising training in respectful care for midwives in all health facilities, for health staff in rural health centres and prefectural hospitals, and improving the equipment of these health facilities would help to reduce mistreatment in obstetrics in Guinea.